Seismic Fragility Estimates of LRB Base Isolated Frames Using Performance-Based Design - Iman Mansouri; Gholamreza Ghodrati Amiri; Jong Wan Hu; Mohammadreza Khoshkalam; Sanaz Soori; Shahrokh Shahbazi (Shock and Vibration)
With improving technology, the idea of using energy dissipater equipment has been strengthened in order to control the structures response in dynamic loads such as wind and earthquake. In this research, we dealt with seismic performance of base isolated structures with lead-rubber bearing (LRB) using incremental dynamic analysis (IDA). For this purpose, 3- and 9-story buildings have been utilized in the SAC project undergoing 22 earthquake records which were far-fault. Plotting the fragility curve for various states of design time period and isolator damping of LRB, it is observed that, by increasing damping, the isolator has not been activated in small spectrum acceleration, which shows that the annual exceedance probability is increased in immediate occupancy (IO) performance level and decreased in life safety (LS) performance level. The results show the reduction of determined failure probability in fragility curves for two levels of performance of uninterrupted use and lateral safety. Likewise obtained results show that, with increasing design time period of isolator, the amount of failure probability is decreased rather than the isolator with smaller design time period, for both LS and IO states. And the isolator illustrates better performance.